Energy partnership Africa – Europe: concentrated solar power between technical realization and ethic responsibility - Schüssler, Frank (ERDKUNDE, 2008)
Concentrating Solar Power (CSP) is technically feasible and develops towards an economically competitive alternative for conventional plants based on fossil fuels. Best locations for CSP can be found in Northern African countries, from which power could be exported to Europe using a new generation of power grids. The idea made it up to the Mediterranean Summit in July 2008, when a “Solar Plan” was initiated. This paper deals with characteristics of CSP technical realisation issues from a European energy demand perspective. Moreover, ethical questions from Northern African countries’ point of view are discussed.